SOLAR ENERGY STORAGE CAPSULE - MATSUO YOSHIHIRO; NITSUTA TSUNEHIRO; ISHIHARA SHIYOUICHI; YAMAMOTO RIYOUICHI (1984)
PURPOSE:To make easier and safer the pipe transportation of liquid in which solar energy storage substances are dissolved and/or dispersed as well as raise the efficiency of heat exchange by a method in which a solar energy storage substance capable of collecting the energy by changing the molecular structure and also of releasing the collected energy in the form of heat by the addition of heat trigger from outside is confined in a shell in a capsule form. CONSTITUTION:A solar energy storage capsule is formed by confining a solar energy storage substance in a capsular shell 1 having a practically high strength enough to withstand deformation by external and internal forces and also incapable of reacting with the solar energy storage substance. The shell 1 also should be impervious greatly to the sun shine, and have as much a small thickness as possible from the point of heat conductivity. The shell 1 is preferably made of polystyrene, polyethylene, etc., and has preferably an average grain size of 0.1-1,000mum range practically. The solar energy storage substance to collect solar energy by the change of molecular structure is roughly divided into the two groups, a valency isomer and a geometrical isomer. The pipe transportation of the solar energy storage capsule is made possible and the efficiency of heat exchange is raised.